Parenting through place‐of‐care disruptions: A qualitative study of parents' experiences of neonatal care - Caroline Cupit; Alexis Paton; Elaine Boyle; Thillagavathie Pillay; Josie Anderson; Natalie Armstrong; the OPTI‐PREM team (Health Expectations)
Abstract Introduction Neonatal care is complex, involving multiple people and technologies within a community of care. When preterm babies are cared for far from home and/or transferred between units, the whole community of care (and particularly parent participation) is disrupted. Although previous studies have captured subjective experiences of parents, there has been little research exploring the material practices undertaken by parents as a consequence of place‐of‐care decisions, or the social organisation of those practices. Methods As part of a wider study exploring optimal place‐of‐care, semistructured interviews were conducted between July 2018 and October 2019 with 48 parents (36 families) with one or more preterm babies (born at 27–31 weeks gestation) cared for in a neonatal unit in the last 12 months. Findings We highlight parents' labour‐intensive and stressful work to: (1) parent in the neonatal care community (an oversight role that goes beyond contemporary notions of ‘involvement’); (2) create continuity amid place‐of‐care disruptions; and (3) adapt to the managerial logics of neonatal care settings. Our analysis focuses on the work generated by managerial systems that organise place‐of‐care decision‐making and other efficiency‐focused practices. Parents are absorbed into negotiating institutional systems and diverted from routine parenting activities. Conclusion Those involved in the organisation and management of neonatal care should take account of how managerial systems impact parents' workload, ability to participate in their baby's community of care and, ultimately, on the wellbeing and development of babies and their families. Patient or Public Contribution The OPTI‐PREM study embedded parents' experiences of neonatal care into the research, through a discrete workstream that employed qualitative methodology to capture parents' experiences—as reported in this paper. The OPTI‐PREM project was also supported by a Bliss volunteer parent panel, which was involved in designing and overseeing the research. Bliss ‘champion[s] the right for every baby born premature or sick to receive the best care by supporting families, campaigning for change and supporting professionals and enabling life‐changing research’ (https://www.bliss.org.uk/about-us/about-bliss). A representative of Bliss is a co‐author of this manuscript, and a parent representative (named in the Acknowledgements) provided feedback during its preparation.